Straight choices the psychology of decision making - Newell, Benjamin R. 1972-; Lagnado, David A. 1962-; Shanks, David R. 1960- (Routledge, 2022)
"Straight Choices provides a fascinating introduction to the psychology of decision making, enhanced by discussion of relevant examples of decision problems faced in everyday life. Thoroughly revised and updated throughout, this edition provides an integrative account of the psychology of decision-making and shows how psychological research can help us understand our uncertain world. The book emphasizes the relationship between learning and decision-making, arguing that the best way to understand how and why decisions are made is in the context of the learning and knowledge acquisition which precedes them, and the feedback which follows. The mechanisms of learning and the structure of environments in which decisions are made are carefully examined to explore their impact on our choices. The authors then consider whether we are all constrained to fall prey to cognitive biases, or whether, with sufficient exposure, we can find optimal decision strategies and improve our decision making. This edition highlights advances made in judgment and decision making research, with additional coverage of behavioral insights, nudging, artificial intelligence, and explanation-based decision making. Written in a non-technical manner, this book is an essential read for all students and researchers in cognitive psychology, behavioral economics, and the decision sciences, as well as anyone interested in the nature of decision making"--
Includes bibliographical references and index
Keywords: Decision making; Learning, Psychology of